ANALISIS PENDAPATAN UMKM, USAHA RUMAH SALAI BENGKULU SEBELUM DAN MASA PANDEMI COVID-19 - Jon Nedi; Bambang Supeno (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
ABSTRACT As a result of the COVID-19 pandemic that emerged in the State of China, in the city of Wuhan, since March 2020, almost all business sectors have been affected, which has been felt by business people, including MSMEs. MSMEs in Indonesia also feel the impact, such as a decrease in sales and a decrease in profits. One of the MSMEs affected is the Bengkulu Salai House, especially MSMEs that produce the manufacture of salai fish, one of which is in Bengkulu City. The purpose of the study was to see the difference in sales income of the Bengkulu Salai House both before and during the covid-19 pandemic. The research method uses a comparative method with a quantitative approach. Secondary data is in the form of financial reports on the Bengkulu Salai House business during the 2018–2021 period. The results showed that there was a difference in sales income before and during the covid-19 pandemic, namely the average sales before the covid-19 pandemic was greater than during the covid-19 pandemic. This shows the influence of the COVID-19 pandemic on sales revenue before and during the Covid-19 pandemic. The findings of this study indicate that MSMEs in Indonesia are vulnerable to the COVID-19 pandemic, to maintain their business continuity, MSMEs need to innovate sales through the use of e-commerce. Keywords: covid-19; MSMEs; sale. ABSTRACT As a result of the COVID-19 pandemic that emerged in the State of China, in the city of Wuhan, since March 2020, almost all business sectors have been affected, which has been felt by business people, including MSMEs. MSMEs in Indonesia also feel the impact, such as a decrease in sales and a decrease in profits. One of the MSMEs affected is the Bengkulu Salai House, especially MSMEs that produce the manufacture of salai fish, one of which is in Bengkulu City. The purpose of the study was to see the difference in sales income of the Bengkulu Salai House both before and during the covid-19 pandemic. The research method uses a comparative method with a quantitative approach. Secondary data is in the form of financial reports on the Bengkulu Salai House business during the 2018–2021 period. The results showed that there was a difference in sales income before and during the covid-19 pandemic, namely the average sales before the covid-19 pandemic was greater than during the covid-19 pandemic. This shows the influence of the COVID-19 pandemic on sales revenue before and during the Covid-19 pandemic. The findings of this study indicate that MSMEs in Indonesia are vulnerable to the COVID-19 pandemic, to maintain their business continuity, MSMEs need to innovate sales through the use of e-commerce. Keywords: covid-19; MSMEs; sale. ABSTRAK Akibat pandemi covid-19 yang muncul di Negara Bagian China, di kota Wuhan, sejak Maret 2020 hampir seluruh sektor bisnis terdampak, yang dirasakan oleh pelaku bisnis tanpa terkecuali UMKM. UMKM di Indoensia juga ikut merasakan dampaknya seperti penurunan penjualan dan penurunan keuntungan. Salah satu UMKM yang terdampak adalah Rumah Salai Bengkulu khususnya UMKM yang memproduksi pembuatan ikan salai salah satunya di kota bengkulu. Tujuan penelitian untuk melihat perbedaan pendapatan penjualan Rumah Salai Bengkulu baik sebelum dan masa pandemi covid-19. Metode Penelitian mengunakan metode komparatif dengan pendekatan kuantitatif. Data sekunder berupa laporan keuangan pada usaha bisnis Rumah Salai Bengkulu selama periode 2018–2021. Hasil penelitian menunjukan bahwa adanya perbedaan pendapatan penjualan sebelum dan masa pandemi covid-19, yaitu rata-rata penjulan sebelum pandemi covid-19 lebih besar di bandingkan masa pandemi covid-19. Hal ini menunjukan adanya pengaruh pandemi covid-19 terhadap pendapatan penjualan sebelum dan masa pandemi covid-19. Temuan penelitian ini menandakan UMKM di Indonesia rentan terhadap pandemi covid-19, untuk mempertahankan kelangsungan usahanya, UMKM perlu melakukan inovasi penjualan melalui pemanfaatan e-commers. Kata Kunci: Pandemi Covid-19; UMKM; Penjualan.